The Load Testing and Numerical Verifying of the Precast Prestressed Girder - Martin Moravcik (Communications - Scientific letters of the University of Zilina, 2007)
Precasting can solve complicated structural details, ambitious demands to quality of surface arrangements and manage hard terms filling at present. The prestressed precast girders are produced to 30.0 m span and are distributed for the realization of big shopping centers. The design and realization of the prestressed precast tie-beam for a skeleton system is presented in this paper. The experimental and numerical analyses were performed to verify the safety and reliable acting of the girder for the next service.